1987
DOI: 10.1002/hed.2890100209
|View full text |Cite
|
Sign up to set email alerts
|

Value of postoperative radiotherapy for thyroid cancer

Abstract: A series of 405 patients with thyroid cancer treated by surgery with or without postoperative radiotherapy from February 1958 through 1979 is reported. The immediate evaluation of the operation was that it was either incomplete or complete. Incomplete surgery implied that there was (1) possible residual tumor in the operative field, the result of difficult dissection of the tumor off the neighboring organs or tissues, as assessed by the surgeon; (2) multiple (more than five) lymph nodes involved; (3) positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…This is in line with our recent metaanalysis (1). Of the 7 reports showing a benefit of RTx in terms of local control (5,11,12,17,30,31) or survival (5,11,19,31,35), none is representative of current medical practice at specialized institutions in the industrialized world.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with our recent metaanalysis (1). Of the 7 reports showing a benefit of RTx in terms of local control (5,11,12,17,30,31) or survival (5,11,19,31,35), none is representative of current medical practice at specialized institutions in the industrialized world.…”
Section: Discussionsupporting
confidence: 87%
“…Some clinicians believe that EXT is useful for those patients with tumors with no RAI uptake [48]. More recent studies revealed that EXT reduced the probability of LR relapse [15,23,[49][50][51]. In the current study, seven patients had EXT (four patients had EXT as part of primary treatment and three patients had EXT at LR relapse).…”
Section: Discussionmentioning
confidence: 56%
“…At present, due to the lack of prospective data and mixed results of retrospective series, the role and indications for EBRT remain controversial, with EBRT still infrequently utilized . In high‐risk patients, it has not been clearly defined whether adjuvant treatment with RAI alone is sufficient .…”
Section: Discussionmentioning
confidence: 99%
“…The current role of external beam radiotherapy (EBRT) in well‐differentiated thyroid carcinomas remains controversial given the conflicting and retrospective nature of published studies . These studies are limited by inherent biases including imbalances due to differences in patient selection, variation in radiation dose, treatment volumes and techniques and publication bias.…”
Section: Introductionmentioning
confidence: 99%